2011
DOI: 10.1186/1477-7525-9-77
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in health-related quality of life after therapy with omeprazole in patients with coronary artery disease and recurrent angina-like chest pain. A double-blind, placebo-controlled trial of the SF-36 survey

Abstract: BackgroundMany patients with coronary artery disease (CAD) have overlapping gastroenterological causes of recurrent chest pain, mainly due to gastroesophageal reflux (GER) and aspirin-induced gastrointestinal tract damage. These symptoms can be alleviated by proton pump inhibitors (PPIs). The study addressed whether omeprazole treatment also affects general health-related quality of life (HRQL) in patients with CAD.Study48 patients with more than 50% narrowing of the coronary arteries on angiography without cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
0
12
0
2
Order By: Relevance
“…It consists of 17 items that can be summed up to a total score. The SF-36 is a generic instrument that has been used extensively to detect and compare health-related quality-of-life impairment in dermatologic and nondermatologic diseases (10)(11)(12)(13)(14). It is composed of 36 items that are related to 8 domains and two composite scores, the 'physical component summary' and the 'mental component summary'.…”
Section: Convergent Validitymentioning
confidence: 99%
“…It consists of 17 items that can be summed up to a total score. The SF-36 is a generic instrument that has been used extensively to detect and compare health-related quality-of-life impairment in dermatologic and nondermatologic diseases (10)(11)(12)(13)(14). It is composed of 36 items that are related to 8 domains and two composite scores, the 'physical component summary' and the 'mental component summary'.…”
Section: Convergent Validitymentioning
confidence: 99%
“…Whereas we cannot rule out that the improvement in SF-36 MCS score at 12 months that we describe represents a placebo effect, of the nine cardiovascular-related studies reported by Frendl and Ware [32], baseline or change in SF-36 MCS scores were reported in six studies. There occurred no significant change in SF-36 MCS score in the placebotreated group in five studies [33][34][35][36][37], whereas in one investigation, the examination of the effectiveness of fludrocortisone on postural hypotension in patients with chronic fatigue syndrome [38], the SF-36 MCS score was increased by approximately 3.5 in the placebo group. Interestingly, in this latter study, the level of depression was quite high, with a mean BDI score of 15.…”
Section: Discussionmentioning
confidence: 81%
“…Budzy!ski et al completed a trial of the SF-36 survey in patients with CAD and recurrent angina-like chest pain. Improved HRQL scores in patients accepting PPI therapy were found in the survey (10). To investigate the patients' overall state of health (physical, emotional and social), the SF-36 survey was also used as an HRQL instrument in our study.…”
Section: Mehta Et Al Investigated Only 24 Patients (24)mentioning
confidence: 99%
“…Furthermore, the most common cardiac drugs used to treat CAD, particularly nitrates, calcium-channel blockers (CCBs) and antiplatelet drugs, may either predispose CAD patients to GERD or aggravate preexisting GERD (7)(8)(9); hence, escalating treatment can increase chest pain, leading the physician to the erroneous conclusion that the CAD is worsening. Previous studies have provided support for the use of acid suppression with proton pump inhibitors in patients with CAD to decrease pain symptoms and improve the general health-related quality of life (HRQL) (10,11). However, most of these studies were conducted in CAD patients with common chest pain, not refractory chest pain.…”
Section: Introductionmentioning
confidence: 99%